Influence of operating parameters and membrane fouling on nutrient transport by FO membrane. (June 2022) - Suleman, Saad Bin; Hai, Faisal I.; Mukhtar, Hamza; Duong, Hung C.; Ansari, Ashley J.
Abstract: The influence of operating parameters (i.e. membrane surface area and water flux) and membrane fouling on FO nutrient retention was examined. A higher water flux and larger membrane surface area significantly improved total ammonia nitrogen retention, owing to the uncoupling of solute and solvent flux and shorter filtration time, respectively. Phosphate retention remained high (>95%) for all experiments. Membrane fouling by real sludge centrate feed solution caused significant water flux decline, and a reduction in total ammonia nitrogen retention was observed at increasing water recovery. Organic fouling by sodium alginate and humic acid also caused significant water flux decline and a lower total ammonia nitrogen retention when compared to a pristine membrane at the same draw solution ionic concentration. However, total ammonia nitrogen retention at the same water flux for a fouled and clean membrane was similar, indicating that membrane fouling had minimal direct influence on nutrient transport. Osmotic backwashing was highly effective in recovering water flux (92% and 85% for model-foulant and real sludge centrate fouled membranes, respectively); however, the reverse salt flux of the membrane increased after fouling/cleaning, indicating possible changes to the membrane integrity. Highlights: Smaller permeate volume per unit membrane area improved nitrogen retention. Phosphate retention remained high (>95%) for all experiments. Membrane fouling had minimal direct influence on nutrient transport. Nitrogen retention reduced at increasing water recovery due to water flux decline. Osmotic backwashing effectively cleaned the membrane but altered membrane performance.